Термостійкість композитів епоксидної смоли з нанографеном модифікованим діоксидом титану - Сігарьова, Н.В.; Місчанчук, О.В.; Горєлов, Б.М. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2023)
The influence of the electronic subsystem of nanographene particles modified with titanium dioxide nanoparticles on the thermal destruction of the polymer matrix is analyzed. The variation in the conductivity of the modifiers made it possible to vary the effect of the metallic electronic system of graphene on thermal destruction by attenuating its effect through the transfer of energy to the electronic subsystem throughout the semiconductor film of anatase and excluding its effect on thermal destruction through a wide-band TiO2 dielectric of rutile form, which is opaque for energy transfer to the electronic subsystem. The application of such films does not affect the thermal processes in which the phonon subsystems of polymer, graphene and crystal modifiers are involved. The method of thermally programmable desorption mass spectrometry investigated the thermal destruction of hybrid composites of epoxy resin with graphene, namely the effect of surface modification of multilayer graphene particles by nanoparticles of pyrogenic titanium dioxide (anatase and rutile forms) on the thermal stability of hybrid epoxy composites in the temperature range of 40 − 800 °C. The activation energies Ed of destruction of atomic fragments of the polymer structure with the value m/z in the range of 16 ‒ 140 D were determined. It has been established that the thermal destruction of fragments of the polymer structure of epoxy resin composites with graphene modified with anatase and rutile forms of titanium dioxide is determined by the peculiarities of thermal transport at the polymer-modifier interfaces. Modification of graphene particles by the anatase form of titanium dioxide leads to increased thermal stability of polymer chains and cross-links in epoxycomposites in the entire range of m/z values of desorbed fragments. Filling the resin with graphene particles coated with the rutile form of TiO2 practically does not affect the intensity of thermal destruction of the composite matrix. The Ed values of different destruction fragments in composites with unmodified and modified graphene are in the range of 50 ‒ 130 kJ/mol. The value of Ed increases by 5 ‒ 10 kJ/mol when the resin is filled with graphene nanoparticles, while the coating of particles with titanium dioxide of the anatase and rutile phases practically does not change the value of Ed of the vast majority of fragments.